The Vase as a Stage? Assteas’ Calyx-Krater from Buccino and the Importance of Visual Parody in Paestan Vase- Painting - Figura, Federico (Römische Mitteilungen, 2022)
In this paper, the problematic relationship between theatre and vase-painting is investigated by focusing on Assteas’ calyx-krater in Buccino. This depicts a parody of the rape of Kassandra. Since the scene has never before been the subject of an iconographic analysis, first a detailed comparison with other southern Italian depictions of the episode is expounded. Besides showing how Assteas’ example is rooted in the southern Italian tradition, all the visual elements that depart from the ‘canonical’ iconography of the rape are identified in order to better understand the geloion. This exercise also helps to challenge the assumption that the image’s origin lies in the treatment of the rape as found in drama. Comparing the Assteas fragment with the corpus of the phlyax vases, this article demonstrates how the former does not in fact represent a theatrical scene, as well as investigating how the comic effect was achieved differently in the visual field. Finally, an analysis of the literary sources entirely supports a non-theatrical origin for the parody, and instead reveals Assteas’ iconopoietic ability to use different comic devices.